Preliminary Study: Kinetics of Oil Extraction from Sandalwood by Microwave-assisted Hydrodistillation - Heri Septya Kusuma; Mahfud Mahfud (Department of Chemical Engineering, Universitas Gadjah Mada, 2016)
Sandalwood and its oil, is one of the oldest known perfume materials and has a long history (more than 4000 years) of use as mentioned in Sanskrit manuscripts. Sandalwood oil plays an important role as an export commodity in many countries and its widely used in the food, perfumery and pharmaceuticals industries. The aim of this study is to know and verify the kinetics and mechanism of microwave-assisted hydrodistillation of sandalwood based on a second-order model. In this study, microwave-assisted hydrodistillation is used to extract essential oils from sandalwood. The extraction was carried out in ten extraction cycles of 15 min to 2.5 hours. The initial extraction rate, the extraction capacity and the second-order extraction rate constant were calculated using the model. Kinetics of oil extraction from sandalwood by microwave-assisted hydrodistillation proved that the extraction process was based on the second-order extraction model as the experimentally done in three different steps. The initial extraction rate, h, was 0.0232 g L-1 min-1, the extraction capacity, CS, was 0.6015 g L-1, the second-order extraction rate constant, k, was 0.0642 L g-1 min-1 and coefficient of determination, R2, was 0.9597.